Assessment Of Long-Term Outcome Among New Smear Positive Pulmonary TB Patients Treated with Intermittent Regimen Under RNTCP – A Retrospective Cohort Study - Dave, Paresh; Rade, Kiran; Modi, Bhavesh; Solanki, Rajesh; Patel, Pradip; Shah, Amar; Vadera, Bhavin (National Journal of Community Medicine, 2013)
Background: Under the Revised National TB Control Programme (RNTCP) of India, treatment of TB is given as thrice weekly regimen following WHO recommended DOTS strategy and the success of treatment is largely declared based on completeness and bacteriological conversion. Once the patient is declared as cured or treatment completed, they are not followed up under the programme unless they come to the health system again with symptoms. Present study was conducted to assess status of patients at 2 years after successful anti-TB treatment under DOTS and to explore any potential impact of treatment irregularity on long term outcome Methods: In this retrospective cohort study, all new smear positive (NSP) pulmonary TB cases declared as cured or treatment completed from were included in the study. They were interviewed, after 24 months from date of declaration of successful treatment, using semi-structured questionnaire. Patient TB treatment card and Tuberculosis registers were also used to collect desired information. Results: A total of 657 out of 706 successfully treated NSP TB patients were included in the study. Out of these, 326 (49.6%) patients had any interruption during their treatment. The average number of doses missed during intensive phase and continuation phase was 7.5 and 11.9 respectively. Average duration of any interruption during treatment was 6.5 days. No significant difference was observed in proportion of treatment interrupters and non-interrupters across demographic variables except for a higher proportion of treatment interruption in patients enrolled from urban district. Out of 657 subjects, 71 (10.85%) had relapse of TB. Another 39 (5.9%) patients died due to TB. These unfavourable outcomes were not significantly different among treatment interrupters and treatment non-interrupters. Conclusion: After being successfully treated, the new smear positive pulmonary TB patients had a very high proportion of relapse of TB. Treatment non-adherence was not significantly associated with long term unfavourable outcomes.